2018
DOI: 10.3762/bjnano.9.41
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of oriented carbon nanotubes in composite materials

Abstract: The orientation and arrangement engineering of carbon nanotubes (CNTs) in composite structures is considered a challenging issue. In this regard, two groups of in situ and ex situ techniques have been developed. In the first, the arrangement is achieved during CNT growth, while in the latter, the CNTs are initially grown in random orientation and the arrangement is then achieved during the device integration process. As the ex situ techniques are free from growth restrictions and more flexible in terms of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 140 publications
1
17
0
Order By: Relevance
“…Magnetization decreased, with the content of MWCNTs, due to the diamagnetic behavior of PLGA. The MWCNTs could be aligned in the PLLA scaffolds under a magnetic field and the magnetization and various thermal, electrical, and optical properties will depend on the orientation of the MWCNTs in the polymer . Some authors have found a superparamagnetic behavior with no coercivity and remanence to PLLA/m‐MWCNTs composites, but with a much higher content of MWCNTs, at around 3 wt %, than the one used in this study to produce our samples.…”
Section: Resultsmentioning
confidence: 88%
“…Magnetization decreased, with the content of MWCNTs, due to the diamagnetic behavior of PLGA. The MWCNTs could be aligned in the PLLA scaffolds under a magnetic field and the magnetization and various thermal, electrical, and optical properties will depend on the orientation of the MWCNTs in the polymer . Some authors have found a superparamagnetic behavior with no coercivity and remanence to PLLA/m‐MWCNTs composites, but with a much higher content of MWCNTs, at around 3 wt %, than the one used in this study to produce our samples.…”
Section: Resultsmentioning
confidence: 88%
“…[29,30] This peak could be attributed to catalyst located on the surface of the CNTs. After acid processing, the intensity of this line decreases and the line completely disappeared for SW_HNO 3 :…”
Section: Characterizationmentioning
confidence: 98%
“…Single‐walled carbon nanotubes (SWCNTs) attract great attention due to their remarkable properties . Since their discovery, SWCNTs have occupied key positions in many areas, including composite materials, conductive and cable fibers, electrochemistry, and other applications. The as‐grown CNTs contain carbonaceous impurities, such as amorphous carbon and carbon nanoparticles, and metal impurities used as catalyst for nanotubes growth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations